Analysing English Language Education Department Students’ Listening Comprehension Difficulties and Strategies - Kristantiningsih, Wulandari; Nurlaily, Nurlaily (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2023)
This research aimed to reveal students' internal and external difficulties in dealing with listening comprehension tests. The research was conducted in the English Language Education Department at a private university in Batam. The total of participants was 32 students, including second and third-year students. The data were analysed through mix-method, using three different instruments: a questionnaire, a listening comprehension test and an interview to collect students' perceptions of their challenges and the listening strategy applied. The students were categorised into two groups: intermediate and advanced students. The findings show that students tend to lose track of long conversation due to a lack of background knowledge and apply an ineffective strategy. Intermediate students utilised the combination of cognitive, metacognitive and socio-affective strategies as advanced students did; however, they still needed to obtain unsatisfactory results due to ineffective strategies. Thus, this research can be useful for educational practitioners, syllabus developers, and students, in general, to be aware of the apprehension and exhibit a suitable strategy to minimise the issue.